Pengembangan E-Booklet Tumbuhan Zingiberaceae Di Desa Mawangi Sebagai Bahan Ajar Tambahan Pada Mata Kuliah Phanerogamae - Wahyuni, Sri Ayu; Amintarti, Sri (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
Zingiberaceae family plants in Mawangi Village are one of the local potentials that can be used as additional teaching materials in locally based Phanerogamae courses that can improve student learning outcomes. This Research and Development aims to describe the suitability, feasibility, readability of the effectiveness of the E-Booklet developed as Additional Teaching Materials in the Phanerogamae Course. This type of research is research and development with a 4D model. The E-Booklet Suitability Test obtained very appropriate results with a score of (4.25), the E-Booklet feasibility test obtained very decent results with a score of (4.5), the readability test obtained very good results with a score of (4.48), the effectiveness test by students was declared a high category with a value of (0.77) based on this The developed E-Booklet can be used as additional teaching materials in the Phanerogamae course..Kata kunci: E-booklet, Phanerogamae, Zingiberaceae